H2 activation on metal oxides promoted by highly dispersed Pd - Yurou Li; Nina Fei; Wenbo Li; Yueqiang Cao; Xiaohu Ge; Sheng Dai; Kelin Yan; Qiang Yuwen; Xinggui Zhou; Weikang Yuan; Xuezhi Duan (Catalysis Communications, 2023)
Promoting the activation of hydrogenation on metal oxide catalysts is crucial but challenging for designing highly efficient heterogeneous metal oxide catalysts. Here, highly dispersed Pd nanoclusters were loaded onto CeO2 surface by incipient-wetness impregnation aiming to enhance the activation of hydrogen and hydrogenation performance of CeO2. Detailed characterizations, including X-ray photoelectron spectroscopy, Raman and H2/D2 isotopic exchange experiments, revealed that the highly dispersed Pd on CeO2 increased the number of oxygen vacancies and thus hydrogen activation. As expected, the Pd/CeO2 catalyst delivered remarkably promoted hydrogenation activity compared to the pristine CeO2 catalyst.